Characterization of Landsubsidence Based on Analysis Geotechnical Data and Groundwater Level North Semarang Area, Central Java Province - Pramudyo, Tulus (Badan Geologi, 2022)
Land subsidence is a geological phenomenon caused by underground compression. This phenomenon develops slowly and not only causes damage to infrastructure but also causes environmental changes and geological disasters. The problem of subsidence in the city of Semarang has caused various damages. This phenomenon is influenced by, among others, the burden of infrastructure and changes in groundwater levels. Subsidence analysis was carried out at two drill points (BM-03 and BM-04). The calculation method based on the loading factor is carried out using the Terzaghi one-dimensional primary consolidation equation with the assumption of additional effective pressure from light structures (residential houses), apartments and runways. Analysis of the calculation of subsidence due to groundwater subsidence using the finite element numerical method with the help of Plaxis 2D 8.6 software. The results of the subsidence analysis based on the loading and subsidence of the groundwater table were then validated with the rate of land subsidence based on subsidence monitoring data using the Geodetic GPS tool for the period 2011 – 2018. Based on the calculation of subsidence in the period 2011 – 2018, the loading is assumed to be 18.4 kN/m2 will cause subsidence in BM-03 of 27.37 cm and BM-04 of 43.49 cm. The decrease in groundwater level for the 2011-2018 period will cause land subsidence in BM-03 of 62.20 cm and BM-04 of 28.90 cm. The results of monitoring the measurement of subsidence that occurred in BM-03 were 96.32 cm and BM-04 were 103.34 cm. The difference in the value of the results of measurements and calculations of subsidence due to loading and subsidence of groundwater is estimated to be caused by natural consolidation factors, with a contribution in BM-03 of 6.75 cm and BM-04 of 30.95 cm.